ENVIRONMENTAL PLASTICITY OF VARIOUS PLUM CULTIVARS UNDER THE CONDITIONS OF CHELYABINSK PROVINCE - A. A. Vasiliev; F. M. Gasymov (Труды по прикладной ботанике, генетике и селекции)
The use of adaptable fruit and berry cultivars significantly increases the environmental sustainability of horticulture. In 2014–2018, the assortment of plum in the Urals was evaluated using the parameters of productivity, environmental plasticity and stability under the conditions of Chelyabinsk Province. The analysis of environmental plasticity and stability helped to identify adaptable cultivars of Chinese plum (Prúnus salicina L.): ‘Altayskaya yubileynaya’ and ‘Uralskaya zolotistaya’. Plastic plum cultivars included cv. ‘Uralskaya zolotistaya’ (yield: 5.62 t/ha; bi = 1.10; Si2 = 25.7), ‘Uralskaya serebristaya’ (5.53 t/ha; 1.16; 21.3) and ‘Manchzhurskaya krasavitsa’ (5.53 t/ha; 1.21; 33.9); their productivity varied in accordance with changes in environmental conditions. Intensive-type cultivars with high responsiveness to the improvement of growing conditions (bi significantly higher than 1) were cvs. ‘Uvelskaya’ (5.62 t/ha; 1.46; 26.8) and ‘Krasnoselskaya’ (5.04 t/ha; 1.35; 45.7). Cv. ‘Zhemchuzhina Urala’ (4.65 t/ha; 0.05; 22.8) belongs to the cultivars with low plasticity (the bi value close to zero); it is characterized by a weak response to a change in environmental conditions. Cv. ‘Altayskaya yubileynaya’ produces the highest yield (6.16 t/ha) due to its plasticity (bi = 0.91), but has low stability (Si2 = 102.5), while cv. ‘Shershnevskaya’ secures rather high productivity (5.23 tons per hectare) due to high stability (Si2 = 32.7) and medium responsiveness to changes in environmental conditions (bi = 0.75).